Applying the Indonesian Urological Association’s recommendations for urology surgery during the COVID-19 pandemics in Dr Sardjito Public Referral Hospital Yogyakarta - Irzan, Muhammad Anwar; Hendri, Ahmad Zulfan; Soerohardjo, Indrawarman (Universitas Gadjah Mada, 2022)
Purpose: Indonesia is a country with many COVID-19 cases distributed in all provinces. There were over 1,860,000 positive cases with 51,612 mortalities as of June 8th, 2021, and 289 deaths were from doctors. The Indonesian Urological Association (Ikatan Ahli Urologi Indonesia, IAUI) has initiatives to protect the members' safety in daily urology practices by issuing recommendations, including urology surgery. The Dr. Sardjito Teaching Hospital as a COVID-19 referral provides urologic surgery services. Method: This study aims to find the pandemic effect in urology surgeries at the COVID-19 Referral Hospital, applying IAUI recommendations. The number of surgeries was compared from 1 year before and after the 2020 IAUI recommendation between April 2019 and April 2021. Results: All categories decreased statistically significantly except fertility. Nine hundred sixty-nine urology surgeries were performed one year before, and 571 surgeries were conducted one year since the recommendation was released. Conclusion: All categories in urology surgery were significantly reduced during a pandemic. Several procedures supposed to delay were still performed under patients’ and urologist’ safety considerations. Urology surgery unit follows the Indonesian Urological Association Recommendations during the COVID-19 pandemic.